2013
DOI: 10.1186/2052-336x-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Influence of under pressure dissolved oxygen on trichloroethylene degradation by the H2O2/TiO2 process

Abstract: BackgroundThe widespread use of trichloroethylene (TCE) and its frequent release into the environment has caused many environmental and health problems. In this study the degradation of TCE at different micromolar concentrations was investigated in a stainless steel reactor with various concentrations of H2O2 and TiO2 at different oxygen pressures and three different pHs.MethodsTo examine the synergistic effect of under pressure oxygen on TCE degradation, the concentrations of H2O2 and TiO2 as well as pH were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…In addition, accumulation and precipitation of TiO 2 under higher catalyst loadings lead to decreasing available catalyst surface for photon absorption and consequently degradation rate decreased. These results are in accordance with the results reported by other researchers who studied the effect of TiO 2 nanoparticles on the degradation of other organic pollutants in various AOPs Dobaradaran et al 2010;Elmolla and Chaudhuri 2010a;Hoseini et al 2013a). In another study performed by Rizzo et al (2009), amoxicillin was completely removed from urban wastewater treatment plant effluent using TiO 2 dosage of 0.8 g/L after 120 min of contact time.…”
Section: Resultssupporting
confidence: 92%
“…In addition, accumulation and precipitation of TiO 2 under higher catalyst loadings lead to decreasing available catalyst surface for photon absorption and consequently degradation rate decreased. These results are in accordance with the results reported by other researchers who studied the effect of TiO 2 nanoparticles on the degradation of other organic pollutants in various AOPs Dobaradaran et al 2010;Elmolla and Chaudhuri 2010a;Hoseini et al 2013a). In another study performed by Rizzo et al (2009), amoxicillin was completely removed from urban wastewater treatment plant effluent using TiO 2 dosage of 0.8 g/L after 120 min of contact time.…”
Section: Resultssupporting
confidence: 92%
“…Hartmann et al (2008) have found that the addition of TiO 2 particles did not cause an increase in the H 2 O 2 formation in the sonication of drug diclofenac, while under the same conditions of Hartmann's study, Keck, Gilbert, and K€ oster (2002) have reported an increase in the formation of H 2 O 2 . The results of our study, however, are in accordance with the results reported by other researchers who studied the effect of TiO 2 nano-particles on the degradation of other organic pollutants in various AOPs Dobaradaran et al 2010;Hoseini et al 2013). Therefore, as the results showed, the optimum amount of TiO 2 catalyst was 250 mg L À1 .…”
supporting
confidence: 94%
“…Basically, increasing in the catalyst concentration may result in increasing the absorbed photons, which in turn increases the number of active sites on the catalyst surface for better adsorption of atrazine herbicide [ 13 ]. Many studies have shown that by increasing the concentration of the catalyst up to an optimal limit results in an increase in the degradation of the pollutants [ 29 31 ]. There was a linear correlation between antibiotic removal and the catalyst concentration.…”
Section: Discussionmentioning
confidence: 99%